2019
DOI: 10.1111/cas.14161
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive immune characterization and T‐cell receptor repertoire heterogeneity of retroperitoneal liposarcoma

Abstract: Retroperitoneal liposarcoma (RLPS) is one of the most common subtypes of retroperitoneal soft tissue sarcomas and lacks effective treatment. This study aimed to provide a thorough profile of immune characteristics of RLPS. This study included 56 RLPS patients. Multisite tumor tissues were collected from 16 patients. Immunohistochemistry was carried out to identify CD4+, CD8+, FoxP3+, CD20+, or programmed cell death‐1 (PD‐1)+ tumor infiltrating lymphocytes (TILs) and  Programmed cell death ligand‐1 (PD‐L1) expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 34 publications
(120 reference statements)
3
50
1
Order By: Relevance
“…A study showed liposarcoma patients exhibit high expression (92-100%) of PDL1 in well-differentiated liposarcoma tumor cells [83,84], and multivariate analysis revealed a PDL1-highly expressed sarcoma was closely associated with shorter survival [85]. In the dedifferentiated liposarcoma, high PDL1 expression was associated with statistically significant unfavorable recurrence-free survival and overall survival rates [86,87].…”
Section: Pd1/pdl1-targeted Therapymentioning
confidence: 99%
“…A study showed liposarcoma patients exhibit high expression (92-100%) of PDL1 in well-differentiated liposarcoma tumor cells [83,84], and multivariate analysis revealed a PDL1-highly expressed sarcoma was closely associated with shorter survival [85]. In the dedifferentiated liposarcoma, high PDL1 expression was associated with statistically significant unfavorable recurrence-free survival and overall survival rates [86,87].…”
Section: Pd1/pdl1-targeted Therapymentioning
confidence: 99%
“… 11 Other groups have also shown that UPS, leiomyosarcoma and LPS patients have increased expression of PD-1/PD-L1, suggesting that these sarcoma subtypes could potentially respond to ICB treatment. 10 14 …”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
“…Studies characterizing T cell infiltrates in bone sarcomas have been published [29][30][31], with more recent studies focussing on soft-tissue sarcomas. A majority of studies find CD8+ T cells to be more abundant [11,[32][33][34] relative to FOXP3+ T regulatory cells [32][33][34][35][36]. When divided based on karyotype complexity, copy number-driven sarcomas (DDLPS [11], leiomyosarcoma [35,37], UPS, and myxofibrosarcoma [38]) had higher T cell infiltration than translocation-associated subtypes [11].…”
Section: T Cell Infiltration: Cd3 Cd4 Cd8 Foxp3mentioning
confidence: 99%